2021
DOI: 10.33963/kp.a2021.0112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a mobile application and smart devices on heart rate variability in diabetic patients with high cardiovascular risk: A sub-study of the LIGHT randomized clinical trial

Abstract: Background: This investigation aims to evaluate the effect of a mobile application and smart devices on frequency and time domains of heart rate variability (HRV) in diabetic patients in 1-year follow-up.Methods: This is post-hoc analysis of a diabetic subgroup of "Lifestyle Intervention usinG mobile technology in patients with high cardiovascular risk: a pragmatic randomized clinical Trial" (LIGHT). One hundred and nine and 118 patients were enrolled in two arms: the intervention plus usual care and the usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“… 59 However, these effects on HRV may still be reversible, as shown in the LIGHT randomized trial studying healthy lifestyle changes in adults with increased cardiovascular risk. 60 The trial showed improvements in both time domain and frequency domain measurements of HRV in patients with diabetes at 1-year follow-up after initiation of lifestyle changes such as improved diet, increased step count, and weight reduction. Although our current review excluded articles that focused on cardiovascular risk or other comorbid diagnoses to focus on psychiatric conditions and their relationship with HRV, these confounding variables may play a role even in patients with primarily psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 93%
“… 59 However, these effects on HRV may still be reversible, as shown in the LIGHT randomized trial studying healthy lifestyle changes in adults with increased cardiovascular risk. 60 The trial showed improvements in both time domain and frequency domain measurements of HRV in patients with diabetes at 1-year follow-up after initiation of lifestyle changes such as improved diet, increased step count, and weight reduction. Although our current review excluded articles that focused on cardiovascular risk or other comorbid diagnoses to focus on psychiatric conditions and their relationship with HRV, these confounding variables may play a role even in patients with primarily psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…These parameters can change in a short time with a healthy lifestyle. 45 COVID-19 can also change the HRV parameters. Increased tonus of parasympathetic parameters is very interesting following COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Combining traditional care with the use of mobile technology offers the possibility of secondary prevention in high-level MI patients for an extended period of at least one year after MI. Research shows the effectiveness of such an action [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%